Seven habits of highly effective people : restoring the character ethic - Covey, Stephen R. (Simon & Schuster New YorkUS, 1990)
Identifies seven habits of successful people, all of which embody basic principles of human effectiveness. Includes: being proactive; thinking win-win; and practising creative co-operation.